Research of the AMT Multi Parameter Fusion Shift Rule of Pure Electric Bus - Yuanguang Jiang; Haonan Li; Jiankun Peng; Zhanjiang Li (Jixie chuandong)
A volumetric Kalman filter estimation algorithm with good real-time accuracy and stability is used to identify the quality of electric bus and road gradient in complex environment. A dynamics model of 4-gear automated mechanical transmission is established, and an economical shift strategy is proposed which is based on the fusion of four parameters: vehicle speed, throttle opening, vehicle quality and road gradient. The simulation results show the identification algorithm proposed can identify vehicle quality and road gradient accurately without adding any sensors. The multi-parameter fusion shifting strategy developed can achieve economical shifting under the condition of guaranteeing vehicle dynamic performance, which can avoid frequent shift, reduce component wear and improve ride comfort to a great extent.